Exploring the relationship between gut microbiota and breast diseases using Mendelian randomization analysis - Wang, Xin; Gao, Haoyu; Zeng, Yiyao; Chen, Jie (Frontiers in Medicine, 2024)
Background Growing evidence suggests a connection between gut microbiota composition and breast diseases, though the precise nature of this association remains uncertain. To investigate a causal relationship between gut microbiota and breast diseases, we utilized a two-way Mendelian randomization (MR) analysis. Methods Four common diseases, including breast cancer, breast cysts, inflammatory disorders of the breast, and infections of the breast associated with childbirth, as well as their subtypes were brought into as the outcomes. Genetic data of the gut microbiota were extracted from genome-wide association studies (GWAS). The primary approach for investigating the association between these genetic factors and gut microbiota was the inverse-variance-weighted (IVW) method with random-effects types. Sensitivity analyses, such as the Cochran Q test, Egger intercept test, and leave-one-out analysis, were conducted to ensure the stability and reliability of the MR findings. Results We discovered plausible causal links between 20 microbial categories and breast diseases with a significance level of p<0.05. Notably, The Family.Rikenellaceae (p value: 0.0013) maintained a significant inverse relationship with overall breast cancer after Bonferroni correction. In the reverse MR analysis, interactions were observed between Genus.Adlercreutzia and ER+ breast cancer. Additionally, the genus Sellimonas, Family.Rikenellaceae and Genus. Paraprevotella were associated with ER+ and overall breast cancer, whereas the genera Dorea was linked to both ER-and overall breast cancer. Family.Prevotellaceae was the sole category correlated with inflammatory breast disorders. Moreover, Genus Eubacteriumruminantiumgroup, Genus Lactococcus and Family Alcaligenaceae were associated with breast cysts, while Genus Anaerofilum, Genus Butyricimonas, Order Coriobacteriales, Order Pasteurellales and Order Verrucomicrobiales showed significant associations with the infections of breast associated with childbirth. No evidence of heterogeneity or horizontal pleiotropy was found. Conclusion Our mendelian randomization analysis affirmed a causal connection between the gut microbiota and breast diseases. Early stool tests may be a viable practice for disease screening to identify people at higher risk of breast diseases.